Genetic strain differences in the development of peritoneal fibroproliferative processes in mice. Issue 3 (May 2014) - Marques, Suzane M.; Castro, Pollyana R.; Campos, Paula P.; Viana, Celso T. R.; Parreiras, Patricia M.; Ferreira, Mônica A. N.; Andrade, Silvia P.
Abstract Fibroproliferative processes are regulated by a wide variety of tissue components and genetic factors. However, whether there are genetic differences in peritoneal fibroproliferative tissue formation, with consequent differences in response to drug treatment, is unclear. We characterize the influence of the genetic background on peritoneal fibroproliferative tissue induced by sponge implants in DBA/1, Swiss, C57BL/6, and BALB/c mouse strains. In addition, responses to dipyridamole in the implants were evaluated. Angiogenesis, assessed by intra‐implant hemoglobin content, was highest in Swiss mice, whereas levels of vascular endothelial growth factor were highest in C57BL/6 mice. The levels of pro‐inflammatory cytokines and of inflammatory enzymes (myeloperoxidase‐ and N‐acetyl‐β‐D‐glucosaminidase) were also strain‐related. The pro‐fibrogenic markers transforming growth factor beta‐1 and collagen were lowest in implants placed in DBA/1 mice, whereas those in C57BL/6 mice had the highest levels. Differential sensitivity to dipyridamole was also observed, with this compound being pro‐angiogenic in implants placed in DBA/1 mice but antiangiogenic in implants placed in Swiss. An overall anti‐inflammatory response was observed in the inbred strains. Antifibrogenic effects were observed only in implants placed in C57BL/6 mice. These important strain‐related differences in the development of peritoneal fibrosis and in response to dipyridamole must be considered in the design and analysis of studies on fibrogenesis in mice.